75.4k views
5 votes
I need a solution

2log_(x)25 - 3 log_(25)x = 1

1 Answer

2 votes
Given

2log_x(25)-3log_(25)(x)=1

first, convert
2log_x(25) to base 25 to match the other term.

2log_x(25)

=2log_(25)(25)/log_(25)(x)

=2*1/log_(25)(x)

Substitute above identity into original equation:

2/log_(25)(x)-3log_(25)(x)=1

Use substiution
u=log_(25)(x)
above equation becomes
2/u-3u=1
multiply by u and solve for u:

3u^2+u-2=0
=> u=2/3 or u=-1

case A:. u=2/3 =>

log_(25)(x)=2/3 => 25^(2/3)=x =>

x=25^(2/3) =8.54987973338348 (approx.)

case B: u=-1 =>

log_25(x)=-1
which does not give a real solution, so reject.

See graph below for confirmation of solution.
I need a solution 2log_(x)25 - 3 log_(25)x = 1-example-1
User Neil Rubens
by
6.2k points